Synthesis, Spectral and Thermal Studies of Some Lanthanide (III) Complexes of 4-[N-(Benzalidene) Amino] Antipyrine Thiosemicarbazone - Singh, Lakshman; Tyagi, Neelam; P. Dhaka, Naresh; Sindhu, S.K. (Asian Journal of Chemistry, 2010)
A new series of sixteen lanthanide(III) complexes of 4-[N-(benzalidene) amino] antipyrine thiosemicarbazone (BAAPTS) with the general composition LnX3·n(BAAPTS) (X = Cl–, n = 2; X = NO–3, n = 1; Ln = La, Pr, Nd, Sm, Gd, Td, Dy and Ho) have been synthesized and characterized by chemical analysis, conductance, molar weight, magnetic moments measurements, infrared and electronic spectra. The ligand BAAPTS behaves as neutral tridentate (N, N, S) ligand. The probable coordination number is nine in these complexes.